Peak width of skeletonized mean diffusivity and its association with age‐related cognitive alterations and vascular risk factors. Issue 1 (1st December 2019) - Lam, Bonnie Yin Ka; Leung, Kam Tat; Yiu, Brian; Zhao, Lei; Biesbroek, J. Matthijs; Au, Lisa; Tang, Yumi; Wang, Kai; Fan, Yuhua; Fu, Jian‐Hui; Xu, Qun; Song, Haiqing; et al.
Abstract: Introduction: Only two studies investigated the associations between peak width of skeletonized mean diffusivity (PSMD) and age‐related cognitive alterations, whereas none of the studies investigated the association with vascular risk factors. Methods: We evaluated 801 stroke‐ and dementia‐free elderlies with baseline and 3‐year follow‐up assessments. Regression analyses were used to assess the association between age‐related cognitive functions and PSMD. Simple mediation models were used to study the mediation effect of PSMD between vascular risk factors and age‐related cognitive outcomes. Results: PSMD was negatively associated with processing speed at baseline and negatively associated with processing and memory scores at 3‐year follow‐up. The association between vascular risk factors and age‐related cognition was mediated by PSMD, as well as other diffusion tensor imaging markers. Discussion: PSMD is preferred over other diffusion tensor imaging markers as it is sensitive to age‐related cognitive alterations and calculation is fully automated. PSMD is proposed as a research tool to monitor age‐related cognitive alterations.